Interdisciplinary Cources in Economics University - N. V. Popova (Вестник Российского экономического университета имени Г. В. Плеханова)
The article deals with substantiation of efficiency of interdisciplinary approach in developing competences in the field of using mathematic methods in economics for graduates of economics universities. The necessity to form such competences arose due to increasing requirements on the part of employers to mathematic training of economists. The research is really acute as shaping skills for using mathematic methods in students’ economic investigations at economics universities is impeded. Key reasons for that include insufficient motivation in a certain part of future economists to study higher mathematics, a limited number of class hours for mathematic subjects, difficult interaction of mathematic and specialty chairs. The author analyzes available in literature examples of using interdisciplinary approach for working-out courses dealing with application of mathematic methods and results of delivering the subject ‘Mathematic Methods of Finance Analysis’ elaborated at the chair of higher mathematics in the Russian Plekhanov University of Economics. To elaborate the subject interdisciplinary approach was used. Interdisciplinary economic and mathematic courses based on fundamental sections of higher mathematics foster understanding of the role of higher mathematics by future economists, help shape necessary competences for graduates of economics universities in the field of using mathematic methods in economics, which can improve the quality of economists’ training and their competitiveness.